Mapping of a major QTL, qBK1Z, for bakanae disease resistance in rice - Lee, Sais-Beul; Kim, Namgyu; Jo, Sumin; Hur, Yeon-Jae; Lee, Ji-Youn; Cho, Jun-Hyeon; Lee, Jong-Hee; Kang, Ju-Won; Song, You-Chun; Bombay, Maurene; Kim, Sung-Ryul; Lee, Jungkwan; et al. (MDPI, 2021)
Bakanae disease is a fungal disease of rice (Oryza sativa L.) caused by the pathogen Gibberella fujikuroi (also known as Fusarium fujikuroi). This study was carried out to identify novel quantitative trait loci (QTLs) from an indica variety Zenith. We performed a QTL mapping using 180 F2:9 recombinant inbred lines (RILs) derived from a cross between the resistant variety, Zenith, and the susceptible variety, Ilpum. A primary QTL study using the genotypes and phenotypes of the RILs indicated that the locus qBK1z conferring bakanae disease resistance from the Zenith was located in a 2.8 Mb region bordered by the two RM (Rice Microsatellite) markers, RM1331 and RM3530 on chromosome 1. The log of odds (LOD) score of qBK1z was 13.43, accounting for 30.9% of the total phenotypic variation. A finer localization of qBK1z was delimited at an approximate 730 kb interval in the physical map between Chr01_1435908 (1.43 Mbp) and RM10116 (2.16 Mbp). Introducing qBK1z or pyramiding with other previously identified QTLs could provide effective genetic control of bakanae disease in rice.